The Community Muralism in Ecuador as a Referential Artistic Experience of a Collaborative Creative Process (Islas, 2025)
Introduction: This article analyzes the collaborative creative process involved in the execution of the mural at the Ángela Rodríguez School in the rural area of Racar, Sinincay, in the city of Cuenca, exploring its impact on the community and on arts education.Methods: A qualitative methodology was used, based on participant observation, interviews, and documentary analysis, collecting experiences from those involved in the process.Results: Co-creation dynamics were identified, strengthening local identity, a sense of belonging, and collective learning.Conclusions: Collaborative art not only transforms physical spaces but also fosters teamwork and community empowerment.
Keywords: collaborative creativity; community participation; community muralism; referential artistic experience; Ecuador